Engajamento colaborativo e gestão de riscos relacionais em redes colaborativas brasileiras - Santos, Washington Romao dos (2020)
Risk management has emerged as an important field of operations management research, due to the greater exposure of organizations to risks, the need to improve cost and inventory management, and the demand for operational agility (AVEN, TERJE, 2016; CHAUDHURI; BOER; TARAN, 2018). Although the topic has received attention in recent years, few explore the relationship between relational risk management and collaborative engagement in interorganizational relationships (DESAI, 2018; REVILLA; SAENZ, 2017). This research proposes to explore the gap between collaborative engagement, using social capital theory, and relational risk management, incorporating rational aspects such as risk information sharing (RIS), analytical decision making (ADM), and risk sharing and opportunities (RSO) by researching the context of Brazilian (buyer-supplier) dyads. Therefore, the thesis defended is that social capital influences collaborative engagement and it influences relational risk management, along with other antecedents RIS, ADM, RSO, assuming the framework proposed by Friday and other authors (2018). This is a quantitative research using structural equation modeling (SEM) using the free software R, the Lavaan 0.6 package and the weighted least squares estimator adjusted for mean and variance (WLSMV). We used a cross-sectional data set collected with Brazilian companies, yielding 402 valid cases. Among the research findings, we found that social capital (relational and cognitive) positively impacts collaborative engagement (R2=0,903), and this, along with risk information sharing, analytical decision making, and risk and opportunity sharing positively impact relational risk management (R2=0,882). The results indicate that the more engaged companies are, they can improve their risk management. Future work may focus on longitudinal studies, analysis of specific contexts and conducting research with multi-case studies